Female countertactics to male feticide and infanticide in a multilevel primate society. (30th April 2022) - Xiang, Zuofu; Yu, Yang; Yao, Hui; Hu, Qinglang; Yang, Wanji; Li, Ming
Abstract: The occurrence of male feticide and/or infanticide represents an extreme case of sexual conflict: an adaptive strategy of male reproduction at the expense of females. Females are predicted to develop numerous countertactics; however, it has remained unclear whether countertactics can effectively shift the balance which likely depends on the social and mating system. We conducted a 15-year, detailed observation of female and male behavior during male replacement in free-ranging golden snub-nosed monkeys ( Rhinopithecus roxellana ) of a multilevel society. We have identified several potential countertactics against feticide and/or infanticide, including pregnant or lactating females staying with ousted males or transferring to stay with the ousted male after being attacked, which lead to 2 of 11 fetuses succumbing to feticide, and extra-unit mating, female joint defense and transferring with their infants to other social units, which lead to 6 of 34 infants succumbing to infanticide. Female joint defenses crucially delay infanticide, providing mothers the opportunity to transfer with their vulnerable infants to another social unit where they have previously mated with the male leader or where they have female relatives. Importantly, in response to mothers starting to transfer, some males cease attacking infants, a change in behavior that is likely to be beneficial to males because during their tenures they can sire future offspring of the mothers who remain. Our findings show how dynamic interactions between males and females can be and how the conditions in multilevel societies can shift the outcome of intersexual conflict from males to females. Abstract : In many primates, males kill unrelated fetuses or offspring to increase their own reproductive success, which bring significant costs to females. This leads to an evolutionary arms-race, where females are predicted to develop countertactics. Here, we show many novel and effective countertactics against feticide or infanticide in golden snub-nosed monkeys of a multilevel society where individuals have social interactions within units as well as within larger bands.